Rapid On-Site Detection of Hepatitis A and Norovirus in Fresh Food Using Duplex RT-RPA and Lateral Flow Assay - Intamaso, Uraiwan; Chutoam, Palatip; Jirasatid, Sani; Wiwekwin, Nisakorn; Saimuang, Kween; Lertjuthaporn, Sakaorat; Kaewdum, Marisa; Jangpatarapongsa, Kulachart (Trends in Sciences, 2025)
Foodborne viruses, such as hepatitis A virus (HAV) and norovirus (NoV), are major public health threats, highlighting the need for rapid, affordable, and user-friendly detection methods. This study introduces a new method that simplifies food extraction and uses duplex RT-RPA combined with a lateral flow assay (LFA) to detect HAV and NoV simultaneously in fresh foods like fresh shellfish, meats, and produce. The RT-RPA conditions and LFA strip design were optimized to improve sensitivity and accuracy. The method was validated for cross-reactivity, sensitivity, and accuracy through interlaboratory testing. It achieved a detection limit of 104 RNA copies per reaction in purified RNA for both HAV and NoV, with no cross-reactivity observed. Among 200 fresh food samples tested, 76.5% (153/200) were contaminated, and 45% (90/200) showed co-contamination with HAV and NoV. Additionally, blind testing by a non-expert achieved 96% accuracy. Compared to existing molecular methods, the main advantages of RT-RPA over RT-PCR and RT-LAMP are its speed, low-temperature operation, robustness and simplicity. Combining RT-RPA with LFA offers a practical and efficient solution for on-site detection of foodborne viruses, with the potential to enhance food safety and reduce virus transmission. HIGHLIGHTS Duplex RT-RPA-LFA detects HAV and NoV in fresh foods within 2 h. High sensitivity with a detection limit of 104 RNA copies per reaction in purified RNA for both viruses. Validated with 96% accuracy in blind testing by non-experts. 5% of tested foods contaminated; 45% co-contaminated with HAV and NoV. Practical, on-site method enhances food safety and reduces virus transmission. GRAPHICAL ABSTRACT